(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрены особенности русловых деформаций, происходящих в нижних бьефах водохранилищ, на примере нижнего бьефа Камского гидроузла. В качестве основного метода оценки русловых деформаций использован гидроморфологический подход. Размеры деформаций за период 1983-2008 гг. определены путем анализа поперечного сечения, продольных профилей и планов. Результатом работ является карта русловых деформаций. К л ю ч е в ы е с л о в а: плотина; русловые деформации; расчет. APPLICATION OF HYDROMORPHOLOGICAL APPROACH TO THE CALCULATION OF CHANNEL DEFORMATIONS IN TAIL-WATER OF КАМA HYDROUNIT In the article features of the channel deformations arotids in tail-water of water basins, on an example Kамa hydrounit are considered. As the basic method of an estimation channel deformations the hydromorphological approach is used. The sizes of deformations for the period 1983-2008 are certain by the analysis the priest-river of section, longitudinal structures and plans. Result of works is the card of the channel deformations.